Vlasov: dvazhdy prokliatyi general - Betke, Ingo; Sergeev, Pavel (Russia : German Wave ; Zebra Berlin, 1995)
This Russian-German co-production touches on one of the most controversial and little-known aspects in the history of Russia's war against Nazi Germany - the story of General Vlasov and his Army. Was he a traitor to his country or a fighter against Stalin's dictatorship? What prompted him to change sides and can he really be considered a collaborator? The film draws on numerous archival documents, which were previously classified and inaccessible to researchers, and on a series of interviews conducted with former members of the Russian Liberation Army (known as ROA), Red Army officers and diplomats, as well as former officers of the British and German armies.
Duration: 01:00:00
With dubbing in Russian